Trimetazidine Inhibits Renal Tubular Epithelial Cells to Mesenchymal Transition in Diabetic Rats via Upregulation of Sirt1 - Yang, Yong; Wang, Yong; He, Zuowen; Liu, Yunchang; Chen, Chen; Wang, Yan; Wang, Dao Wen; Wang, Hong (Frontiers in Pharmacology, 2020)
Trimetazidine (TMZ), as a metabolic regulator, is effective in treatment of coronary atherosclerotic heart disease with rare side effects in the clinic for long years. Interestingly, studies have shown that TMZ protects against several acute kidney injuries (AKI). However, the effect of TMZ on chronic kidney diseases (CKD) remains unknown. This study aimed to investigate the role of TMZ in diabetic nephropathy (DN) and its potential mechanisms. A rat model of DN was established in male Sprague-Dawley rats by streptozotocin (STZ) intraperitoneal injection. Experimental rats were separated into 3 groups: control, DN and DN + TMZ treatment. Metabolic parameters, pathological features and renal function markers were evaluated after 20 weeks of diabetes induction. In vitro experiments, the effect of TMZ on high fat and high glucose (HFG) induced or TGFβ1-induced epithelial-to-mesenchymal transition (EMT) was examined in HK-2 cells. Our results showed that TMZ could maintain renal function without affecting hemodynamic and plasma metabolic levels in diabetic rats. The effect was associated with a reversion of pathological progression of DN, especially for tubulointerstitial fibrosis. EMT is an important contributor to renal fibrosis. In this study, we investigated the role of TMZ in the process of EMT in DN. Mechanistically; TMZ attenuated HFG-induced EMT by relieving oxidative stress via deacetylation forkhead box O1 (FoxO1) in a Sirt1-dependent pathway. And it suppressed TGFβ1-induced EMT by deacetylating Smd4 in a Sirt1-dependent manner. Moreover, our study found that TMZ upregulated Sirt1 expression by increasing the expression of nicotinamide phosphoribosyl transferase (Nampt), which is a rate limiting enzyme for nicotinamide adenine dinucleotide (NAD+) generation by salvage pathway. And the increased NAD+ promoted Sirt1 expression. In conclusion, TMZ can prevent renal dysfunction and pathogenesis of tubulointerstitial fibrosis in DN, partly by inhibition of EMT via FoxO1/ROS pathway and TGFβ/Smad pathway in a Nampt/NAD+/Sirt1 dependent manner.